Adesão à terapia antirretroviral, autoeficácia e qualidade de vida relacionada à saúde em pessoas vivendo com HIV/AIDS - Bomfim, Isabella Gerin de Oliveira (Universidade Federal de São Carlos, 2019)
Introduction: AIDS remains a major public health issue. There was control of new cases of HIV infection in the second half of the 1990s and a new increase with peak in 2010. This increase is probably due to the risk behavior in the population, the existence of undiagnosed individuals and a low adherence to antiretroviral therapy . The management of antiretroviral therapy aims to offer recommendations for preventing transmission, treating infection and improving quality of life. It is a dynamic, complex, multifactorial process that is comprehensive and difficult to measure, and there are several ways described and validated to measure adherence to antiretroviral therapy (ART), with different applications. Objective: To assess adherence and risk factors associated with adherence to antiretroviral treatment in people living with HIV / AIDS. Methods: Descriptive cross-sectional study. Adult individuals diagnosed with HIV / AIDS using antiretroviral therapy for at least three months in SAE of São Carlos city were included. RESULTS: A total of 220 patients were evaluated, of which 58% were men, with a mean age of 43 years, 41% with a primary education, 26% men who have sex with men - MSM, 55% in the AIDS stage, 91% with more than one year of follow-up. Adherence to antiretrovirals in the sample studied was 62%. The factors associated with adherence in the univariate analysis were living alone, to be a man who has sex with men, not having an active sex life, do not smoke, having a CD4 count greater than 350 cels / mm3, having an undetectable HIV1 plasma load, having no history of treatment interruption and having a score greater than 101 on the Self-efficacy Expectation Scale. Factors associated with adherence in the multivariate regression analysis were do not smoke, having no active sex life, and undetectable last viral load test. Conclusion: The results may contribute to the identification of groups at higher risk of nonadherence to ART and emphasize the need for investment in measures that promote greater adherence to treatment.
Antiretroviral therapy adherence, self-efficacy and health-related quality of life in people living with HIV/AIDS
Keywords: HIV; Adesão à medicação; Antirretroviral; Autoeficácia; Qualidade de vida; Medication Adherence; Antiretroviral Therapy; Self Efficacy; Quality of Life; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS